2017
DOI: 10.3389/fimmu.2017.01172
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-Ribose)Polymerase-1 in Lung Inflammatory Disorders: A Review

Abstract: Asthma, acute lung injury (ALI), and chronic obstructive pulmonary disease (COPD) are lung inflammatory disorders with a common outcome, that is, difficulty in breathing. Corticosteroids, a class of potent anti-inflammatory drugs, have shown less success in the treatment/management of these disorders, particularly ALI and COPD; thus, alternative therapies are needed. Poly(ADP-ribose)polymerases (PARPs) are the post-translational modifying enzymes with a primary role in DNA repair. During the last two decades, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 198 publications
2
37
0
Order By: Relevance
“…It must be stressed that the degree of cytokine accumulation during EVLP correlates with poor outcomes after LTx . Our finding of reduced cytokines with 3‐AB implicates therefore a key role of PARP in this process, in line with the reported pro‐inflammatory actions of PARP, notably in the lungs …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It must be stressed that the degree of cytokine accumulation during EVLP correlates with poor outcomes after LTx . Our finding of reduced cytokines with 3‐AB implicates therefore a key role of PARP in this process, in line with the reported pro‐inflammatory actions of PARP, notably in the lungs …”
Section: Discussionsupporting
confidence: 83%
“…22 Our finding of reduced cytokines with 3-AB implicates therefore a key role of PARP in this process, in line with the reported pro-inflammatory actions of PARP, notably in the lungs. 23,24 To be clinically relevant, the effects of any drug on a lung graft ex vivo should translate into an improved outcome after LTx in vivo. To date, such evidence is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the FDA-approved PARP1 inhibitor, olaparib, has been reported to protect against the LPS (Lipopolysaccharide)-induced acute lung and kidney injuries in a NF-κB-dependent manner in mice [49]. Numerous pre-clinical studies demonstrated that PARP1 inhibitors play an essential role in a range of inflammatory injuries and related diseases, especially the lung inflammatory disorders including ARDS (Acute Respiratory Distress Syndrome), COPD (Chronic Obstructive Pulmonary Disease) and asthma [40,46,50,51]. All these studies suggest that PARP1 inhibitors are of high relevance to the treatment of the novel pneumonia caused by SARS-CoV-2 infection, possibly via their roles in modulating inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a complex, multifactorial disorder of lungs, mainly characterized by airway inflammation, immunoglobulin E (IgE) generation, and production of type 2 helper T cell (Th2) cytokines, namely IL‐4, IL‐5, and IL‐13 (comprehensively reviewed ). Repeated allergen exposure primarily results in accumulation of inflammatory cells mainly eosinophils, lymphocytes, and neutrophils in the lungs.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(ADP‐ribose) polymerase (PARP; EC 2.4.2.30) is a family of nuclear enzymes consisting of 18 members that are primarily involved in DNA repair (comprehensively reviewed ). Indeed, PARP‐1 (an ambient member of the PARP family) is activated upon DNA damage and is reported to be engaged in various physiological functions such as chromatin remodeling, transcription, and regulation of inflammatory pathways .…”
Section: Introductionmentioning
confidence: 99%